Achieving stable and high-rate quasi-solid-state sodium batteries through strengthened P-O covalency and interface modification in Na3Zr2Si2PO12 - Taiguang Li; Butian Chen; Tenghui Wang; Chong Liu; Wen Yin; Qianjiang Mao; Dongxu Zhou; Yongmei Hao; Xiangfeng Liu (Nature Communications)
Abstract Solid-state sodium metal batteries have attracted great interest because of their improved safety and abundant Na resources. However, the interfacial resistances and instabilities induced by parasitic reactions, together with Na dendrite issues, result in reduced rate capability and poor cycling stability. Here, we address these challenges by intrinsically inhibiting parasitic interfacial redox reactions through enhanced P-O covalency in Na3Zr2Si2PO12 (NZSP) with Na2SiF6 incorporation, wherein the high electronegativity of F strengthens P-O covalency. Additionally, SnF2 coating provides a sodiophilic surface and stabilizes the NZSP interface, which is essential for effective electrochemical cycling. This integrated approach significantly reduces interfacial impedance to 2.0 Ω cm2, enabling stable Na plating/stripping for 3600 hours at 0.5 mA cm-2/0.25 mAh cm-2. The full cell with Na3V2(PO4)3 positive electrode demonstrates stable cycling with high-rate capability (87.5% capacity retention after 2500 cycles at 1 C and 96.1% capacity retention after 1200 cycles at 5 C). This study sheds light on the development of high-performance quasi-solid-state sodium batteries.